The impact of submaximal fatiguing exercises on the ability to generate and sustain the maximal voluntary contraction - Lebesque, Loïc; Scaglioni, Gil; Martin, Alain (Frontiers in Physiology, 2022)
Neuromuscular fatigability is a failure to produce or maintain a required torque, and commonly quantified with the decrease of maximal torque production during a few seconds-long maximal voluntary contraction (MVC). The literature shows that the MVC reduction after exercises with different torque-time integral (TTI), is often similar. However, it was shown that after a fatiguing exercise, the decline in the capacity to sustain the maximal voluntary contraction for 1 min (MVC1-MIN) differs from the decrease in the capacity to perform a brief-MVC, suggesting that this latter can only partially assess neuromuscular fatigability. This study aims to highlight the relevance of using a sustained MVC to further explore the neuromuscular alterations induced by fatiguing exercises with different TTI. We used two contraction intensities (i.e., 20% and 40% MVC) to modulate the TTI, and two exercise modalities [i.e., voluntary (VOL) and electrical induced (NMES)], since the letter are known to be more fatiguing for a given TTI. Thirteen subjects performed a plantar-flexors MVC1-MIN before and after the fatiguing exercises. A similar MVC loss was obtained for the two exercise intensities despite a greater TTI at 40% MVC, regardless of the contraction modality. On the other hand, the torque loss during MVC1-MIN was significantly greater after the 40% compared to 20% MVC exercise. These findings are crucial because they demonstrate that maximal torque production and sustainability are two complementary features of neuromuscular fatigability. Hence, MVC1-MIN assessing simultaneously both capacities is essential to provide a more detailed description of neuromuscular fatigability.